A global perspective on sustainable pathways for biogas adoption - K. Biró; K.S. Woon; W. Ounsaneha; C. Rattanapan (Global Journal of Environmental Science and Management)
Biogas technology has been developed worldwide in recent decades to provide affordable, secure, and clean energy in rural and developing regions. The technology presents various advantages, as it can be utilized for heating, generating power, and functioning as both a fuel and a raw material in the chemical manufacturing process. However, its widespread adoption remains hindered by complex social, economic, and environmental challenges. Local acceptance is increasingly becoming a critical factor for biogas projects and the transition to renewable energy. The objective of this systematic review is to explore and assess the diverse factors that contribute to the acceptance of biogas, utilizing publications from the Scopus, Web of Science, and PubMed databases for analysis. The study examined the connections among authors, disciplines, and geographic regions to contextualize the findings within the global framework. A visualization of similarities and Java-based software was utilized to map the trends in co-authorship, keyword co-occurrence, and thematic developments from 2013 to 2024. Adopting the preferred reporting items for systematic reviews and meta-analyses methodology, 1,358 studies were screened, resulting in 20 peer-reviewed publications meeting the inclusion criteria. A total of 248 factors influencing the acceptance of biogas were identified and clustered along the three sustainability dimensions. Biogas projects are influenced by social, environmental, and economic factors in distinct ways depending on the country or region. The weight scores within each dimension were normalized and the overall score of the studies were calculated, allowing for a comparability of the studies. The finding reveals that social factors are the most significant determinants of biogas adoption, including public trust, procedural justice, and community involvement, accounting for 45 percent of the total. Financial aspects, including incentives, operational costs, and market conditions represent 31 percent. The remaining 24 percent was comprised of environmental factors that received the lowest overall scores, including emission reduction, resource compatibility, and land use impacts. This indicates that the environmental drivers are less emphasized than the other two dimensions. The study emphasizes the critical significance of local governance, the engagement of stakeholders, and the implementation of strategic communication in facilitating the uptake of biogas. Perceived benefits, equity in decision-making, and accessible financial mechanisms emerged as key enablers, while barriers included mistrust, lack of awareness, uneven decision-making, and cost constraints. The significance of tailoring strategies to local conditions is highlighted by regional disparities. In Europe, the focus is on policy alignment, stakeholder governance, and sophisticated infrastructure, whereas developing regions emphasize affordability, education, and resource accessibility. The study highlights the necessity of an integrated approach that considers social, economic, and environmental dimensions, providing actionable insight to ensure equitable and sustainable biogas implementation.